Trades access common core. Line B, Employability skills, Competency B-4, Describe the apprenticeship system - Lidstone, Rod; Camosun College; British Columbia. Ministry of Technolgy, Innovation and Citizens' Services; BC Open Textbook Project; BCcampus (Ministry of Technology, Innovation and Citizens' Services, 2015)
"This Competency provides the information necessary for you to understand the trades training system and how to explore any trades you may be interested in. Careers in the trades can be highly rewarding. Forecast shortages in skilled trades mean that there will be significant opportunities for new workers to enter many of the trades. The following list of lines and competencies was generated with the goal of creating an entry-level trades training resource, while still offering the flexibility for lines to be used as stand-alone books. Line B - Employability Skills. B-1 Apply Study and Learning Skills, B-2 Describe Expectations and Responsibilities of Employers and Employees, B-3 Use Interpersonal Communication Skills, B-4 Describe the Apprenticeship System."--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
"Copyright Camosun College"--P. 2.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on January 7, 2016).
Keywords: Apprenticeship programs -- Textbooks; Employability -- Textbooks; Electronic books